Drug utilization pattern in ENT OPD of government tertiary care teaching hospital in Raigarh - Y., Kishore Kumar; Cheekavolu, Chakrapani; Obulesu, G. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The prospective, observational study was designed to assess the prescribing pattern of drug usage in ENT outpatient department in various diseases conditions. Methods: Medication utilization Form has been designed based on a WHO format. The patient’s details including patient particulars, diagnosis, investigations, drug details and information regarding the indication for prescribing agents. Results: Total 200 prescriptions were analysed, 70% were males and 30 % were females, respectively. The most common disease reported was CSOM in 31 (15.5 %) patients followed by otitis externa 25 (12.5%), pharyngitis 21 (10.5%), URTI patients 20 (10.0%). Antibiotics used were: amoxicillin-clavulanate 200 (57.3%), cefixime 37 (10.6%), levofloxacin 34 (9.74%), cefixime clavulanate 30 (8.59%), cefuroxime 13 (3.72%). The most commonly used NSAID are diclofenac and paracetamol. Conclusions: Prescribing pattern of usage of antibiotics are more compared to other drugs, amoxicillin with clavulanic acid are most commonly prescribed antibiotics in various ENT diseases, usage of brand name are higher than the generic name.